ANOTHER ADDITION TO THE COVID-19 ASSOCIATED COMPLICATIONS-MUCORMYCOSIS - Mahmood, Fizza; Mahmood, Muhammad Usama; Riaz, Aniqa (Journal of Ayub Medical College Abbottabad, 2022)
New manifestations of coronavirus disease are appearing over time. The association between coronavirus and mucormycosis must be given serious consideration. Without early diagnosis and treatment, there may be rapid progression of the disease, with high mortality from complications. We present a case of a 40-year-old male who presented with rhino-orbital-cerebral mucormycosis and COVID-19 infection. With this case, we highlight the importance of considering mycotic coinfection in COVID-19 patients with diabetes and the significance of its early diagnosis and treatment.